Implementasi Produktivitas Wakaf Pada Pemberdayaan Pesantren Daarul Qolam Binjai - Muhammad Azizi Akbar; Yenni Samri Julianti Nasution (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Waqf plays an important role and offers significant contributions in various sectors, especially in the advancement of Islamic boarding school education. The purpose of this study is to explore the implementation of productive waqf development as a means of educational empowerment at the Daarul Qolam Binjai Islamic Boarding School. The approach used in this study is qualitative descriptive. This research was conducted at the Daarul Qolam Islamic boarding school in Binjai, where data was collected through observation, interviews, and documentation, while data verification was carried out through triangulation techniques. The results of the study indicate that first, the strategy of developing productive waqf for educational empowerment at the Daarul Qolam Binjai Islamic Boarding School aims to increase the independence of the pesantren and develop human resources as business actors through various assets and programs managed by the Daarul Qolam Binjai Islamic Boarding School Waqf Agency. Second, the productive waqf mechanism is implemented through a systematic, detailed, and in accordance with legal provisions. Third, the development of productive waqf plays a crucial role in the progress and welfare of the education of students at the Daarul Qolam Binjai Islamic Boarding School. The form includes the allocation of productive waqf utilization which is prioritized on strengthening Islamic boarding schools and support for education, including the provision of logistics, infrastructure development, facilities and infrastructure, and Islamic boarding school operations, which are partly sourced from the surplus of productive waqf assets.